Atmospheric tank failures: Mechanisms and an unexpected case study. Issue 4 (6th February 2017) - Schmidt, Michael S.
Abstract : The literature on catastrophic failures of low‐pressure tanks focuses on the ignition of explosive mixtures in the vapor space of those tanks, and rightly so, because most catastrophic failures of atmospheric tanks involve explosions of such mixtures. Moreover, there is a general sense in the industry that other than explosions of flammable mixtures, the only other hazard associated with low‐pressure tanks is the occasional dramatic implosion of a vessel that is inadequately protected against vacuum. In fact, there are a number of mechanisms that can lead to the catastrophic failure of a low‐pressure tank that have nothing to do with combustion or unprotected vacuum. Under certain circumstances, even a tank equipped with an atmospheric vent and containing nothing other than salt water can explode, with disastrous impacts. This article reviews the mechanisms for catastrophic failure of low pressure tanks, both implosion and explosion, and serves as a reminder for experienced process safety practitioners and as a tutorial for new process safety practitioners of what to look for during a hazard review. It also includes a case study of an atmospheric caustic tank explosion that resulted from a previously unreported mechanism that involved neither combustion nor vacuum. © 2017 American Institute of Chemical Engineers Process Saf Prog 36: 353–361, 2017